2007
DOI: 10.1186/1472-6963-7-85
|View full text |Cite
|
Sign up to set email alerts
|

Why, and how, mixed methods research is undertaken in health services research in England: a mixed methods study

Abstract: Results: 18% (119/647) of HSR studies were classified as mixed methods research. In the documentation, comprehensiveness was the main driver for using mixed methods research, with researchers wanting to address a wider range of questions than quantitative methods alone would allow. Interviewees elaborated on this, identifying the need for qualitative research to engage with the complexity of health, health care interventions, and the environment in which studies took place. Motivations for adopting a mixed met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
266
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(273 citation statements)
references
References 30 publications
2
266
1
4
Order By: Relevance
“…Such role is critical in the Islamic culture where an effort will not be blessed without family, particularly parent and husband sanction (Muhamad et al, 2011;Norsa'adah et al, 2012). A literature review done by O'Cathain et al (2007) found that one of the barrier for breast cancer screening in Asian women was "inability to act without husband permission". As permission from husband and parent is very crucial in decision making, healthcare professionals should include them in health education and information giving programme to encourage mutual understanding and support among patients, husband and family.…”
Section: Discussionmentioning
confidence: 99%
“…Such role is critical in the Islamic culture where an effort will not be blessed without family, particularly parent and husband sanction (Muhamad et al, 2011;Norsa'adah et al, 2012). A literature review done by O'Cathain et al (2007) found that one of the barrier for breast cancer screening in Asian women was "inability to act without husband permission". As permission from husband and parent is very crucial in decision making, healthcare professionals should include them in health education and information giving programme to encourage mutual understanding and support among patients, husband and family.…”
Section: Discussionmentioning
confidence: 99%
“…Health research in the past has been predominated by quantitative approaches (Weaver and Olson, 2003;O'Cathain, 2007). Two main approaches are naturalistic or qualitative and positivist or quantitative approaches differ in their ontological, epistemological and methodological perspectives (Proctor 1998;Weaver and Olson, 2006).…”
Section: Philosophical Underpinnings For the Studymentioning
confidence: 99%
“…Given the dearth of evidence about patient and family caregiver experiences with opioids for dyspnea, it was appropriate to use a qualitative approach. We supplemented this approach with quantitative measures to further describe participants and maximize comprehensiveness, 10 an approach consistent with current calls for mixed-methods approaches to evaluate dyspnea in advanced disease [11][12][13] and the benefit of palliative care interventions. 1 3 To identify physicians' attitudes about and experience with prescribing opioids in this context, we used a single qualitative approach and collected basic demographic information.…”
mentioning
confidence: 99%